Applying Eurithmy Exercises to Develop Students’ Senseof Rhythm in Music Lessons: Performance Research in the 7th Grade - Šauklė, Ieva (Jaunųjų mokslininkų darbai, 2024)
The article reviews the ideology of the É. Jaques-Dalkroze musical-rhythmic education system, the eurythmy method is described, as well as its practical significance in developing a sense of rhythm through a case study, in the 7th grade music lessons of X Pro-Gymnasium.The results of the qualitative activity study revealed that students with good coordination, reaction, and motor skills have a good sense of rhythm. The sense of rhythm of weakly sensitive/anti-arrhythmic research participants during the practice of eurythmy exercises developed positively: the reaction of the participants improved, the internal sense of time duration, body movements became more expressive during the rhythm, and anti-rhythmicity no longer appeared during the practice of eurythmy exercises. Also, after practicing eurythmy exercises, better social skills, emotional state, and positive classroom climate of the participants were observed.